Electrospinning preparation and electrical and biological properties of ferrocene/poly(vinylpyrrolidone) composite nanofibers - Chai, Ji-Hong; Wu, Qing-Sheng (Beilstein Journal of Nanotechnology, 2013)
Nanofibers containing ferrocene (Fc) have been prepared for the first time by electrospinning. In this paper, Fc was dispersed uniformly throughout the poly(vinypyrrolidone) (PVP) matrix for the purpose of combining the properties of PVP and Fc. The effects of solvents and Fc concentration on the morphologies and diameters of nanofibers were investigated. In the DMF/ethanol solvent, the morphologies of the obtained nanofibers significantly changed with the increase of Fc concentration. The results demonstrated that the morphologies of the nanofibers could be controlled through adjusting solvents and Fc concentration. Scanning electron microscopy (SEM) showed that the diameters of the obtained composite fibers were about 30–200 nm at different Fc concentrations. Thermogravimetric analysis (TGA) results confirmed the presence of ferrocene within the PVP nanofibers. X-ray diffraction (XRD) results showed that the crystalline structure of Fc in the fibers was amorphous after the electrospinning process. A biological evaluation of the antimicrobial activity of Fc/PVP nanofibers was carried out by using Gram-negative Escherichia coli (E. coli) as model organisms. The nanofibers fabricated by this method showed obvious antibacterial activity. Electrochemical properties were characterized based on cyclic voltammetry measurements. The CV results showed redox peaks corresponding to the Fc+/Fc couple, which suggested that Fc molecules encapsulated inside PVP nanofibers retian their electrochemical activity. The properties and facile preparation method make the Fc/PVP nanofibers promising for antibacterial and sensing applications.
Keywords: composites; electrochemistry; electrospinning; membranes; porous materials